Teaching the common law in Quebec: reflections on the proliferation of separate, suppletive degree programs - Sérafin, Stéphane (Pontificia Universidad Católica del Perú. Departamento Académico de Derecho. Centro de Investigación, Capacitación y Asesoría Jurídica, 2018)
This paper seeks to explore some of the reasons why [the suppletive curriculum] model, which favors the elective, separate training of students in a second legal tradition, remains by far the dominant model of common law teaching in Quebec.
La enseñanza del derecho consuetudinario en Quebec: reflexiones sobre la proliferación de titulaciones separadas y supletorias
Keywords: Derecho comparado; Enseñanza del derecho comparado; Comparative law; https://purl.org/pe-repo/ocde/ford#5.05.00